Sedition in Upper Canada: Contested Legality - Wright, Barry (Labour/Le Travailleur, 1992)
The paper examines the uses of sedition law in Upper Canada. Largely neglectedby historians, sedition prosecutions were frequently resorted to by the government between the 1790s and the 1820s, and are suggestive of larger patterns in the Canadian experience of dissent and national security measures. The essay focuses on the series of cases connected to the Gourlay affair as the best illustrations of the various facets of sedition law in the province. The availability and use of sedition law by the government to regulate provincial politics, and in particular, to delineate the loyal community and its enemies, was contested, sometimes successfully, byopposition leaders. The formal claims of the legal system, while helping to legitimate the exercise of power, also limited the repression to some extent. Thecases brought to the fore the tension between the rule of law and discretionary power, played out in terms of issues about executive control over criminal prosecutions, jury selection and the scope fo the jury's verdict, and judicial independence.These contested issues appear to have had some degree of broader public engagement based on popular understandings of the British constitution. The sedition cases not only suggest the importance of law in the exercise of authority, but also the importance of the courts as a site of oppositional struggles.